Job performance based on training, compensation, and discipline in DISHUB Ogan Komering Ilir - Rusli Yanto; Tien Yustini (Institute of Computer Science (IOCS), 2026)
This research aims to analyze and prove the influence of training, compensation, and discipline on job performance at the Department of Transportation of Ogan Komering Ilir Regency, both partially and simultaneously. The research method is quantitative with a survey, confirmatory, and verificative approach. This research is classified as associative research related to the relationships among variables. The population consists of 110 employees, all of whom were taken as the research sample using a saturated sampling technique. The types of data used include primary and secondary data, collected through observation, questionnaire-based interviews, and documentation. The data analysis technique is multiple linear regression using SPSS v.30. The results show that training, compensation, and discipline have a positive and significant effect on improving job performance, both partially and simultaneously. These three variables have a substantial (strong) relationship of 84.2% with the improvement of job performance. This research contributes to developing comprehensive human resource management science and further research in this field. Improving job performance can be done by simultaneously paying attention to aspects of training, compensation, and discipline